2010
DOI: 10.1247/csf.10009
|View full text |Cite
|
Sign up to set email alerts
|

p120-catenin Is Essential for N-cadherin-mediated Formation of Proper Junctional Structure, thereby Establishing Cell Polarity in Epithelial Cells

Abstract: ABSTRACT. The role of p120-catenin in the function of classical cadherins is still enigmatic despite various studies. To elucidate its role, we examined the effect of p120-catenin on the N-cadherin-mediated localization of junctional proteins in epithelial cells in this study. Cadherin-deficient MIA PaCa-2 epithelial cells did not show linear localization of tight junction proteins ZO-1 and occludin. When N-cadherin was expressed in these cells, however, the resultant transfectant cells revealed strong cell ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Using a polyclonal anti-PAK4 antibody [14], we observed that PAK4 was strongly enriched at cell-cell junctions in U2OS, Panc-1 and MDCK cells (Fig 1A), and in none of these cells did we find co-staining with focal adhesion markers. The PAK4 signal at cell-cell junctions overlapped but did not colocalize precisely with the adherens junction marker p120-catenin (Fig 1B), which binds to conventional cadherins [45]. …”
Section: Resultsmentioning
confidence: 99%
“…Using a polyclonal anti-PAK4 antibody [14], we observed that PAK4 was strongly enriched at cell-cell junctions in U2OS, Panc-1 and MDCK cells (Fig 1A), and in none of these cells did we find co-staining with focal adhesion markers. The PAK4 signal at cell-cell junctions overlapped but did not colocalize precisely with the adherens junction marker p120-catenin (Fig 1B), which binds to conventional cadherins [45]. …”
Section: Resultsmentioning
confidence: 99%
“…Various reports have observed that loss of a-catenin, b-catenin, or p120-catenin perturbs the integrity of AJ and destroys the adhesion. [55][56][57][58] Three subtypes of a-catenin, aE, aN, and aT, are known.…”
Section: Expression Of N-cadherin In Neuroepithilial Cells and Radialmentioning
confidence: 99%
“…67,73 According to the site of Numb, N-cadherin-based AJ is formed in the sub-apical region. 67,73 Numb is known to interact with p120-catenin, 58,77 so p120 catenin may be involved in the localization of N-cadherin-based AJ by Numb. , p120-catenin (p120), a-catenin (a), and a cytoskeleton, F-actin are connected to each other to construct AJ.…”
Section: 61mentioning
confidence: 99%
“…The asymmetric distribution of cadherin-based adherens junctions resulting from their absence at the front is a distinguishing feature of leader cells and is sufficient to induce front -rear polarization of the cytoskeleton and the cytoplasm in vivo and in vitro (Desai et al 2009;Dupin et al 2009;Ozaki et al 2010;Dumortier et al 2012;Ng et al 2012;Oubaha et al 2012;Weberet al 2012). …”
Section: Leader Cell Front -Rear Polaritymentioning
confidence: 99%
“…The mechanisms that underlie cadherin-dependent front -rear polarization depend on the activity of cdc42, Rac, and PI3K, and the interaction of cell-cell junctions with the actin cytoskeleton (Desai et al 2009;Ozaki et al 2010;Dumortier et al 2012) and appear quite conserved as they were shown in both epithelial and nonepithelial cells, typically downstream from E-cadherin and N-cadherin, respectively. However, detailed analysis of these pathways is complex owing to the fact that many signaling pathways, in particular Rho GTPases, control both front -rear polarity, as discussed previously, and cell-cell adhesion (Fig.…”
Section: Cadherin-dependent Polarizationmentioning
confidence: 99%